A precious issue [in the endowment ownership of the benefit Retrieved from the manuscript [The Precious Issues] Hassan Sadr Al-Din bin Hassan Hadi Al-Mousawi Al-Kazemi (1272 AH - 1354 AH) (Journal of the College of Basic Education, 2023)
In the name of God, and prayers and peace be upon the Messenger of God, and praise be to God, Lord of the worlds, we praise Him, we seek His help, we seek guidance from Him, and we seek His forgiveness, we seek refuge in God from the evils of ourselves and from the evils of our deeds, whoever God guides will not misguide him, and whoever he misleads you will not find a guiding guardian for him, after that. In this religious research that I put in the hands of your presence, I am discussing an important religious jurisprudence issue in the Muslims’ faith and their lives, which is (Waqf is ownership of the benefit), and what it contains of some provisions, for example: the concept of benefit and that it is a usufruct contract not ownership, and other related provisions mentioned In the issue, which every Muslim, male and female, must understand what it means, and I relied in this research on the mothers of jurisprudence books of the Imami school of thought, in investigating the issue. To arrange it on the introduction, the study section, and the investigation section, where I made my work in it composed of two parts, as follows: The study section, which is composed of a topic, the first topic: introducing the author’s life, and it included six demands, the first requirement: his name and lineage, the second requirement: his titles and family The third requirement: his birth and death, the fourth requirement: his travels, the fifth requirement: his elders and disciples, the sixth requirement: his travels, the second topic: the verified text, the first requirement: a description of the manuscript copies, the second requirement: the name of the manuscript and documenting its attribution to its author, the reason for its authorship, and the requirement Third: methodical investigation. And the third topic: is the verified text, from the manuscript (Nafias Al-Masaa’il), the issue of (Waqf is ownership of the benefit). The purpose of my research is for the Muslim to know that the purpose of the endowment is not to own the endowment himself, but rather to own its benefit, following the Sunnah of the Prophet - may God bless him and his family and grant them peace - and I do not conceal from you that delving into religious issues is a vast matter, and a vast sea, and it is our duty as Muslims And researchers, that we know its parties and learn the fundamentals of our religion, and from this idea I came up with the idea of my research so that my message reaches everyone who wants to benefit and learn more about his religion. Our Lord reward and reward.